A process model for concurrent conceptual design of space systems. Issue 4 (12th April 2021) - Knoll, Dominik; Fortin, Clement; Golkar, Alessandro
Abstract: This work presents a model of the process of conceptual design studies which use the concurrent engineering approach. Concurrent conceptual design is an integrated system development approach, to rapidly explore feasible design solutions by parallelizing the work of experts. This approach is characterized by a multidisciplinary team of experts collaborating in a co‐located manner. Albeit the conceptual design phase requires creative problem solving, teamwork requires coordination, and would profit from a shared understanding of the design process. Based on a survey among experts from 15 different organizations, and practice documented in literature, we propose a model of the underlying design process. This work extends our previous work on a coordination method for concurrent design and provides validation of the process model via case studies and expert interviews. The proposed process model is formalized in SysML diagrams. It can be used to help program coordinators and train engineers of different disciplines on the methodology of concurrent conceptual design, as well to serve as a baseline for implementing the methodology in new organizations.